When the minor resides outside the EU: some problematic issues. (Notes to the order of the Court of Appeal of Valencia of 23th September 2024) - Carrillo Pozo, Luis F. (CUADERNOS DE DERECHO TRANSNACIONAL, 2025)
When a dispute involves issues of parental responsibility relating to a child resident in a non-EU Member State and international jurisdiction rules other than those of Regulation 2019/1111 are applied, areas of conflict arise between the latter and the 1996 Hague Convention (e. g., the temporal projection of the prorrogation clause in favor of a Member State’s court when there is a change of residence), implementation problems that arise from the simple fact that the LEC is not conceived in terms of international litigation (e. g., when the plaintiff is the public prosecutor) or the functioning of the LOPJ (residual forums). These issues are addressed in the following pages.
Keywords: International jurisdiction; Residual competencies; Habitual residence of the child in a third State